2010
DOI: 10.1080/00207233.2010.507477
|View full text |Cite
|
Sign up to set email alerts
|

The impact of climate change on aquatic risk from agricultural pesticides in the US

Abstract: We investigate how climate change may affect the acute and chronic toxicity risk to aquatic species from agricultural pesticides in 32 States of the US. We combine climate change projections from the Canadian and Hadley climate model, statistically estimated relationships between pesticide applications and climate and weather variables, and the environmental risk indicator REXTOX developed by the OECD. On average, we find that climate change is likely to increase the toxicity risk to aquatic species by 47% bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…These calculations took various aspects of environmental and human health into account. Koleva and Schneider (2009a) estimated the potential changes in aquatic risk due to climate change for 12 coastal U.S. states on the basis of values of toxicity for single species of standard test organisms (Daphnia, algae, and fish). They also predicted, averaged for each state, a general increase in aquatic risk of 16-27% from 2000 to 2100.…”
Section: Future Rp and Ermentioning
confidence: 99%
“…These calculations took various aspects of environmental and human health into account. Koleva and Schneider (2009a) estimated the potential changes in aquatic risk due to climate change for 12 coastal U.S. states on the basis of values of toxicity for single species of standard test organisms (Daphnia, algae, and fish). They also predicted, averaged for each state, a general increase in aquatic risk of 16-27% from 2000 to 2100.…”
Section: Future Rp and Ermentioning
confidence: 99%
“…Preharvest pests destroy between 15% and 60% of crops globally (Oerke 2006) and contribute to uncertainty in the supply and prices of food (Waterfield and Zilberman 2012). Although agricultural pesticides can reduce these losses, they also have a range of negative effects on human (Alavanja et al 2004) and ecosystem health (Foley et al 2005, McKinlay et al 2008, Koleva and Schneider 2010, Kattwinkel et al 2011, Beketov et al 2013. Many of the negative externalities associated with pesticide use are determined by the intensity of exposure .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Pandey et al [38] also reported some cases of pesticides monitoring in other places in the world, such as: (1) coastal marine sediment in Singapore; (2) Ebro river delta, Mediterranean Sea; (3) Paranoa lake in Brazil; (4) Coastal lagoon watershed in Argentina; (5) Bay of Ohuira in Mexico; (6) Haleji lake in Pakistan; (7) some stream sediment in Spain; (8) Lake Orta sediments in Italy; (9) Uluabat lake in Turkey and (10) Pearl river estuary in China etc. Pesticides are in detectable level in the UK groundwater [5] while, in the US, it has been reported that 100% of major rivers and streams and 33% of major aquifers contained at least one pesticide at detectable levels [39].…”
Section: Discussionmentioning
confidence: 99%